Salicylic Acid Accumulation in Tomato Root Induced by Endopytic Bacteria and Exogenous Salicylic Acid Response to Ralstonia syzygii subsp. indonesiensis Infection - Nababan, Triwanto; Lisnawita, Lisnawita; Safni, Irda (Contributions of Central Research Institute for Agriculture, 2024)
Ralstonia syzygii subsp. indonesiensis causes bacterial wilt disease is a soil-borne pathogen that causes serious damage and major losses in tomato production. To overcome this, the use of Arthrobacter sp. and Bacillus thuringiensis as biological elicitors and salicylic acid as a chemical elicitor were teste their capacity to induce tomato plants to become resistant. Experiments were carried out on the susceptible tomato cultivar "Servo F1" in sterilized soil to test the elicitor's effectiveness in triggering plant defense mechanisms in response to salicylic acid accumulation in afflicted roots. Arthrobacter sp. and salicylic acid treatments significantly reduced the disease severity due to bacterial wilt compared to control treatment within three weeks after inoculation. Tomato with once week application intensity was also better than every two weeks application intensity. The AUDPC value showed by Arthrobacter sp. was 1449.7 with an application intensity every two weeks and 148 with an application intensity once a week compared to control with an AUDPC value of 4962.9. Furthermore, endophytic bacteria and salicylic acid can induce salicylic acid accumulation in pathogen-inoculated tomato roots. The results show that the elicitor is either biological or chemicals play an important role as inducers of plant defenses, thereby reducing bacterial wilt disease.